Literacy and Numeracy Ecosystem: A Case Study of Learning Quality Transformation in the Suburban Area of Semarang City - Ayu Nyoman Murniati, Ngurah; Sulanjari, Bambang; Haryati, Titik (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to analyze the acceleration of secondary education quality based on the harmonization of managerial policies and instructional flexibility, specifically examining the use of the Education Report Card as a pedagogical navigation instrument. This study employed a qualitative approach conducted in a suburban area to explore and analyze the policy harmonization and instructional practices in both public and private secondary schools. The results reveal a dichotomy in achievement: public schools excel in digital aspects, while suburban private schools face obstacles in developing students' critical thinking. The findings confirm that literacy and numeracy success depends on cross-subject synergy and teachers' mental well-being rather than just facilities. Consequently, this study practically recommends adopting a "Cross-Discipline Integration" strategy and reorienting budgets to strengthen non-exact science teacher competencies to eliminate math anxiety through a visual classroom ecosystem. The novelty of this study lies in shifting the paradigm of education quality from a facility-centric view to an integrated approach focused on cross-subject synergy and teacher well-being. Furthermore, it introduces the "Peer Mentoring in the Recovery Room" model and the application of ethnomathematics as new future research pathways to align teachers' emotional stability with the authenticity of student learning outcomes in suburban contexts.